A diamond-metal composite material with directional heat conduction function, a preparation method and application thereof

CN122879583APending Publication Date: 2026-10-09山东中科润晶新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611020617.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,现有技术中金刚石增强相多为不规则颗粒或八面体晶形,在金属基体中随机分布,难以形成定向的导热通路,热量在复合材料内部传导时,需频繁穿越金刚石-金属界面,产生较大的界面热阻,金刚石的优异导热性能无法充分发挥

Benefits of technology

[0018]本发明提供的一种具有定向导热功能的金刚石-金属复合材料、制备方法及应用,利用金刚石六面体方晶的几何特性,无需复杂定向工艺即可实现沿(100)晶面的垂直导热,结构简单、易于实现;单层规则排列消除了颗粒堆叠界面,减少界面热阻,提高导热效率;复合材料厚度可通过金刚石粒径和金属层厚度精确控制,设计灵活;具有高热导率和可调热膨胀系数,与半导体芯片匹配性好,适用于电子封装热沉、功率器件散热和航空航天热管理系统等多种热管理场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879583A_ABST
    Figure CN122879583A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of diamond composite material, and proposes a diamond-metal composite material with directional heat conduction function, a preparation method and application, which comprises a metal matrix and diamond cubic crystals, the diamond cubic crystals are arranged in a single layer in the metal matrix and are not stacked, the angle between the normal direction of the (100) crystal face of the diamond cubic crystal and the plane of the diamond-metal composite material is ≤10°, and a heat conduction path dominated by the (100) crystal face of the diamond cubic crystal is formed in the thickness direction of the diamond-metal composite material. The present application utilizes the geometric characteristics of the diamond hexahedral cubic crystal, and realizes vertical heat conduction along the (100) crystal face without complex directional process; the single-layer regular arrangement eliminates the particle stacking interface, reduces the interface thermal resistance, and improves the heat conduction efficiency; the present application has high thermal conductivity and adjustable thermal expansion coefficient, and has good matching with semiconductor chips, and is suitable for various thermal management scenes such as electronic device heat dissipation substrate and high-power semiconductor packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of diamond composite materials, and particularly relates to a diamond-metal composite material with directional thermal conductivity, its preparation method and application. Background Technology

[0002] As electronic devices rapidly evolve towards higher power density and miniaturization, heat dissipation has become a bottleneck restricting the performance improvement of electronic components. Although traditional heat dissipation materials such as copper and aluminum have high thermal conductivity (copper approximately 400 W / (m·K) and aluminum approximately 237 W / (m·K)), they are insufficient to meet the higher heat dissipation performance requirements of next-generation high-power devices.

[0003] Diamond possesses the highest thermal conductivity among known materials (reaching over 2000-2200 W / (m·K)). Combining it with metals to prepare diamond-metal composites is an effective way to balance high thermal conductivity with good processability. However, in existing technologies, the diamond reinforcing phase is mostly composed of irregular particles or octahedral crystals, randomly distributed within the metal matrix. This makes it difficult to form directional thermal conduction pathways. When heat is conducted within the composite material, it must frequently cross the diamond-metal interface, resulting in significant interfacial thermal resistance, thus preventing the full utilization of diamond's excellent thermal conductivity. Summary of the Invention

[0004] This invention addresses the technical problems existing in the aforementioned diamond materials by proposing a diamond-metal composite material with directional thermal conductivity, its preparation method, and its application.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The present invention provides a diamond-metal composite material with directional heat conduction function, comprising a metal matrix, wherein diamond particles are disposed in the metal matrix, the metal matrix is ​​copper, aluminum or copper-aluminum alloy, the diamond particles are diamond square crystals and are hexahedral square crystals, the diamond square crystals are arranged in a single layer in the metal matrix and do not stack, the spacing between adjacent diamond square crystals is 0.5 to 2.0 times the particle size of the diamond square crystals; the bottom surface of the diamond square crystals forms a planar contact with the metal matrix, and the angle between the normal direction of the (100) crystal plane of at least 90% of the diamond square crystals and the plane where the diamond-metal composite material is located is ≤10°, forming a heat conduction path dominated by the (100) crystal plane of the diamond square crystals in the thickness direction of the diamond-metal composite material.

[0006] Preferably, the half-width at half-maximum (WHM) of the X-ray rocking curve of the (100) crystal plane of the diamond square crystal is less than 0.5°.

[0007] Preferably, the density of the diamond-metal composite material is greater than 98%, wherein the integral number of the diamond cubic crystal is 30%-70%.

[0008] Preferably, the thickness H of the diamond-metal composite material includes the particle size d of the diamond square crystal, the thickness t1 of the metal layer above the diamond square crystal, and the thickness t2 of the metal layer below the diamond square crystal, H = d + t1 + t2, wherein the particle size d of the diamond square crystal is 50~500μm, and t1 and t2 are each 10μm~200μm.

[0009] A method for preparing a diamond-metal composite material with directional thermal conductivity includes the following steps:

[0010] S1. Prepare a grid mold. The grid mold is made of metal material and has regularly arranged mesh holes. Spread diamond square crystals on the grid mold. Vibrate or scrape to make the diamond square crystals fall into the mesh holes and form a single-layer regular matrix. Control the spacing between adjacent diamond square crystals to be 0.5 to 2.0 times the particle size of the diamond square crystals. The angle between the (100) crystal plane normal direction of the diamond square crystal and the normal of the mold surface is ≤10°.

[0011] S2. Fill the grid mold with metal powder of the same material as the grid mold into the grid mold in which diamond square crystals are arranged, and vibrate to make the metal powder fill the gaps between the diamond square crystals to obtain the filled blank.

[0012] S3. The filled blank and the grid mold are hot-pressed and sintered together. The hot-pressing and sintering temperature is lower than the melting point of the metal, the pressure is 30~100 MPa, and the holding time is 10~60 minutes until the grid mold and the filled metal powder are fused together to obtain diamond-metal composite material.

[0013] Preferably, the mesh shape of the grid mold matches the bottom surface shape of the diamond square crystal, and the side length of the mesh of the grid mold is less than 1.2 times the side length of the bottom surface of the diamond square crystal, thus restricting the rotation of the diamond square crystal.

[0014] Preferably, the thickness of the grid mold is 30% to 50% of the height of the diamond square crystal, so that the upper part of the diamond square crystal is higher than the surface of the grid mold.

[0015] Preferably, the vibration frequency in step S2 is 50~200 Hz and the duration is 30~180 seconds.

[0016] A diamond-metal composite material with directional thermal conductivity was prepared by a method for preparing diamond-metal composite material, which is applied to heat sinks for electronic packaging, heat dissipation of power devices and thermal management systems for aerospace.

[0017] Compared with the prior art, the advantages and positive effects of the present invention are as follows:

[0018] This invention provides a diamond-metal composite material with directional thermal conductivity, its preparation method, and its application. Utilizing the geometric characteristics of the hexahedral cubic diamond crystal, vertical thermal conductivity along the (100) crystal plane can be achieved without complex orientation processes, resulting in a simple and easy-to-implement structure. The single-layer regular arrangement eliminates the particle stacking interface, reduces interfacial thermal resistance, and improves thermal conductivity. The thickness of the composite material can be precisely controlled by the diamond particle size and the metal layer thickness, allowing for flexible design. It has high thermal conductivity and an adjustable coefficient of thermal expansion, making it well-matched with semiconductor chips and suitable for various thermal management scenarios such as electronic packaging heat sinks, power device heat dissipation, and aerospace thermal management systems. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 The diagram shows the material characterization of the diamond-metal composite materials prepared in Examples 1 to 3 and the comparative examples. Detailed Implementation

[0021] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.

[0022] Numerous specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways than those described herein, and therefore the invention is not limited to the specific embodiments disclosed in the following specification. Example 1

[0023] This embodiment provides a diamond-metal composite material with directional thermal conductivity and its preparation method, including the following specific steps:

[0024] S1. Prepare a grid mold and a diamond square crystal. The diamond square crystal is a hexahedral square crystal with a grain size of 150 μm. Its (100) crystal face is complete, the half-width of the X-ray rocking curve is 0.3°, and the surface roughness Ra is 20 nm. The grid mold is made of metal material and has regularly arranged mesh holes. The shape of the mesh holes of the grid mold matches the shape of the bottom surface of the diamond square crystal. The side length of the mesh holes of the grid mold is less than 1.2 times the side length of the bottom surface of the diamond square crystal, which restricts the rotation of the diamond square crystal. The thickness / groove depth of the grid mold is 50 μm, which is 33.33% of the height of the diamond square crystal, so that the upper part of the diamond square crystal is higher than the surface of the grid mold.

[0025] Diamond square crystals are spread on a grid mold, and the diamond square crystals fall into the mesh holes by vibration or scraping to form a single-layer regular matrix without stacking. The spacing between adjacent diamond square crystals is 200μm (about 1.33 times the particle size), and the angle between the (100) crystal plane normal direction of at least 90% of the diamond square crystals and the normal of the mold surface is controlled to be ≤10°.

[0026] S2. Fill the grid mold with a metal matrix of the same material as the grid mold, which is copper, into the grid mold with diamond square crystals arranged in it; vibrate at a frequency of 50~200 Hz for 30~180 seconds to fill the gaps between the diamond square crystals with metal powder to obtain the filled blank.

[0027] S3. The filled blank, together with the grid mold, is hot-pressed and sintered. The hot-pressing and sintering temperature is lower than the melting point of the metal, the pressure is 30~100 MPa, and the holding time is 10~60 minutes, until the grid mold and the filled metal powder are fused together to obtain the diamond-copper composite material blank.

[0028] The diamond-metal composite material obtained in Example 1 was characterized as follows: Figure 1 As shown, a sample of a certain area was cut from a diamond-metal composite preform. The thickness of the diamond-metal composite was approximately 300 μm (diamond particle size + upper copper layer + lower copper layer); the diamond volume fraction was approximately 55%; the thermal conductivity measured by laser scintillation was 723 W / (m·K); and the coefficient of thermal expansion was 7.8 × 10⁻⁶. -6 / K (25-200℃); Density: greater than 99%.

[0029] The thickness H of the diamond-metal composite material includes the particle size d of the diamond square crystal, the thickness t1 of the metal layer above the diamond square crystal, and the thickness t2 of the metal layer below the diamond square crystal. H = d + t1 + t2. In Example 1, the particle size d of the diamond square crystal is 150 μm, t1 is 100 μm, and t2 is 50 μm. Example 2

[0030] This embodiment provides a diamond-metal composite material with directional thermal conductivity and its preparation method. It is the same as Example 1 except for the following differences, which are: the hexahedral diamond square crystals used in S1 have a particle size of 300 μm, with complete (100) crystal planes, a half-width at half-maximum of 0.4° on X-ray rocking curve, and a surface roughness Ra of 35 nm; the diameter of the through holes in the grid mold is 320 μm, the depth is 100 μm, and the hole spacing is 450 μm (about 1.5 times the particle size). The diamond square crystals are made to fall into the holes by scraping; in S2, both the metal powder / matrix and the grid mold are made of aluminum; in S3, the filled blank and the grid mold are placed together in a vacuum hot press furnace at a temperature of 600℃ and a pressure of 30 MPa for 30 minutes; finally, a blank of diamond-aluminum composite material is obtained.

[0031] The diamond-aluminum composite material obtained in Example 2 was characterized as follows: Figure 1 As shown, the thickness of the diamond-aluminum composite material is approximately 500 μm (300 μm diamond grain size + 100 μm each for the upper and lower aluminum layers); the diamond volume fraction is approximately 48%; the thermal conductivity measured by laser scintillation is 612 W / (m·K); and the coefficient of thermal expansion is 11.2 × 10⁻⁶. -6 / K (25-200℃); density greater than 98.5%.

[0032] Example 3

[0033] This embodiment provides a diamond-metal composite material with directional thermal conductivity and its preparation method. Except for the following differences, it is the same as Example 1. The difference lies in the diamond square crystal grain size and arrangement parameters, specifically including: the diamond square crystal grain size in S1 is 80 μm, the half width at half maximum of the X-ray rocking curve is 0.25°; the arrangement spacing between adjacent diamond square crystals is 100 μm (approximately 1.25 times the grain size).

[0034] The diamond-copper composite material obtained in Example 3 was characterized as follows: Figure 1 As shown, the thickness of the diamond-copper composite material is approximately 160 μm (diamond particle size 80 μm + upper copper layer 50 μm + lower copper layer 30 μm); the diamond volume fraction is approximately 42%; the thermal conductivity is 658 W / (m·K); and the coefficient of thermal expansion is 8.9 × 10⁻⁶. -6 / K; density greater than 99%. Comparative Example

[0035] This comparative example provides a diamond-copper composite material, which differs from Example 1 in that irregularly shaped diamond particles are used instead of diamond hexahedral crystals with a particle size of about 150 μm. Other conditions are the same as in Example 1.

[0036] Characterization of the diamond-copper composite material obtained in the comparative example: Figure 1 As shown, the diamonds in the diamond-copper composite material are randomly distributed and cannot be arranged in a regular pattern; the thermal conductivity is 212 W / (m·K), which is significantly lower than that of Example 1, and the coefficient of thermal expansion is 13.5 × 10⁻⁶. -6 / K, some diamond particles have poor contact with the matrix, resulting in large pores.

[0037] In the diamond-metal composite material with directional thermal conductivity provided in Examples 1 to 3 and its preparation method, the half-width at half-maximum (WHM) of the X-ray rocking curve of the (100) crystal plane of the diamond square crystal is controlled to be less than 0.5°, which is beneficial to improving the interfacial bonding strength of the diamond-metal composite material and improving the density. Furthermore, when the diamond-metal composite material is subjected to thermal cycling and external impact, the interface is not easy to crack or peel off, and the overall bending, tensile and impact resistance is significantly improved. At the same time, the regular crystal plane interface has fewer defects and a high effective contact area ratio, resulting in a sharp drop in interfacial thermal resistance and an overall composite thermal conductivity that is much higher than that of the comparative diamond-metal composite material.

[0038] Furthermore, this invention utilizes the geometric properties of hexahedral diamond crystals to achieve vertical heat conduction along the (100) crystal plane without complex orientation processes. This forms a heat conduction path dominated by the (100) crystal plane of the diamond crystals along the thickness direction of the diamond-metal composite material. The single-layer regular arrangement eliminates particle stacking interfaces, reduces interfacial thermal resistance, and improves thermal conductivity. The thickness of the diamond-metal composite material can be precisely controlled by the diamond particle size and metal layer thickness, offering good controllability. It also possesses high thermal conductivity and an adjustable coefficient of thermal expansion, making it well-suited for semiconductor chip compatibility and applicable to various thermal management scenarios such as electronic packaging heat sinks, power device heat dissipation, and aerospace thermal management systems.

[0039] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A diamond-metal composite material with directional thermal conductivity, comprising a metal matrix, wherein diamond particles are disposed in the metal matrix, and the metal matrix is ​​copper, aluminum, or a copper-aluminum alloy, characterized in that... The diamond particles are diamond cubic crystals and are hexahedral cubic crystals. The diamond cubic crystals are arranged in a single layer in the metal matrix and do not stack. The spacing between adjacent diamond cubic crystals is 0.5 to 2.0 times the particle size of the diamond cubic crystals. The bottom surface of the diamond cubic crystals forms a planar contact with the metal matrix. At least 90% of the diamond cubic crystals have an angle ≤10° between the normal direction of the (100) crystal plane and the plane where the diamond-metal composite material is located, forming a heat conduction path dominated by the (100) crystal plane of the diamond cubic crystals in the thickness direction of the diamond-metal composite material.

2. The diamond-metal composite material with directional thermal conductivity according to claim 1, characterized in that, The half-width at half-maximum (WHM) of the X-ray rocking curve of the (100) crystal plane of the diamond square crystal is less than 0.5°.

3. A diamond-metal composite material with directional thermal conductivity according to claim 2, characterized in that, The density of the diamond-metal composite material is greater than 98%, wherein the integral number of the diamond cubic crystal is 30%-70%.

4. A diamond-metal composite material with directional thermal conductivity according to claim 3, characterized in that, The thickness H of the diamond-metal composite material includes the grain size d of the diamond square crystal, the thickness t1 of the metal layer above the diamond square crystal, and the thickness t2 of the metal layer below the diamond square crystal, H = d + t1 + t2, wherein the grain size d of the diamond square crystal is 50~500μm, and t1 and t2 are each 10μm~200μm.

5. A method for preparing a diamond-metal composite material with directional thermal conductivity, characterized in that, Includes the following steps: S1. Prepare a grid mold. The grid mold is made of metal material and has regularly arranged mesh holes. Spread diamond square crystals on the grid mold. Vibrate or scrape to make the diamond square crystals fall into the mesh holes and form a single-layer regular matrix. Control the spacing between adjacent diamond square crystals to be 0.5 to 2.0 times the particle size of the diamond square crystals. The angle between the (100) crystal plane normal direction of the diamond square crystal and the normal of the mold surface is ≤10°. S2. Fill the grid mold with metal powder of the same material as the grid mold into the grid mold in which diamond square crystals are arranged, and vibrate to make the metal powder fill the gaps between the diamond square crystals to obtain the filled blank. S3. The filled blank and the grid mold are hot-pressed and sintered together. The hot-pressing and sintering temperature is lower than the melting point of the metal, the pressure is 30~100 MPa, and the holding time is 10~60 minutes until the grid mold and the filled metal powder are fused together to obtain diamond-metal composite material.

6. The method for preparing a diamond-metal composite material with directional thermal conductivity according to claim 5, characterized in that, The mesh shape of the grid mold matches the bottom surface shape of the diamond square crystal, and the side length of the mesh of the grid mold is less than 1.2 times the side length of the bottom surface of the diamond square crystal, thus restricting the rotation of the diamond square crystal.

7. The method for preparing a diamond-metal composite material with directional thermal conductivity according to claim 6, characterized in that, The thickness of the grid mold is 30% to 50% of the height of the diamond square crystal, and the upper part of the diamond square crystal protrudes above the surface of the grid mold.

8. The method for preparing a diamond-metal composite material with directional thermal conductivity according to claim 7, characterized in that, The vibration frequency in step S2 is 50~200 Hz, and the duration is 30~180 seconds.

9. An application of a diamond-metal composite material with directional thermal conductivity, characterized in that, The diamond-metal composite material prepared by the method of any one of claims 5 to 8, which has a directional thermal conductivity, is suitable for various thermal management scenarios such as heat sinks for electronic packaging, heat dissipation of power devices, and thermal management systems for aerospace.